Supplier selection using Fuzzy DEA credibility constrained and relative closeness index: A case of Indonesian manufacturing industry - Ilyas Masudin; Candra Adelia Mawarni; Rahmad Wisnu Wardana; Dian Palupi Restuputri (Cogent Business & Management, 2023)
Supplier selection plays a crucial role in enhancing the competitiveness and operational efficiency of manufacturing industries. In the Indonesian manufacturing sector, where market conditions are dynamic and complex, the need for an effective supplier selection methodology is particularly critical. The suggested method converts conventional DEA (Data Envelopment Analysis) models into fuzzy events through the application of credibility measures. Additionally, the relative closeness (RC) index is employed to enhance the differentiating capability of traditional DEA. This article incorporates three input criteria and five output criteria. The findings suggest that higher values of the RC Index correspond to superior performance by the supplier. Furthermore, the study's outcomes reveal that the credibility index influences the RC index. Imposing stricter credibility constraints can diminish the value of the RC index.
Keywords: 650; credibility constraint; Fuzzy DEA; MCDM; relative closeness; supplier evaluation